Proactive Policing as a Strategy to Prevent Youth Brawls - Arini Ayatika Aprilya Fidthy (Universitas Islam Darul Ulum Lamongan, 2023)
Cases of brawls between groups of teenagers are not a new phenomenon in the midst of social life. Actions of brawls carried out by groups of delinquent youth continued to flourish and also resulted in injuries and even fatalities. Technological developments also affect the method of carrying out brawls. Groups of teenagers use social media accounts to challenge each other to take brawls at locations that are also determined through social media messages. The timing of brawls is also not only carried out during the day but also at night and early in the morning as in several examples of brawl cases that occurred in 2023. This can disrupt security and public order in the community. Prevention strategies using the Proactive Policing method need to be carried out to prevent brawls from occurring. The Proactive Policing strategy in this case is carried out by forming a joint patrol team to carry out systematic patrol activities in the community and also cyber patrols to monitor social media accounts that have indications of provoking brawls.